2020
DOI: 10.1101/2020.04.13.20064295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benefits and Risks of Chloroquine and Hydroxychloroquine in The Treatment of Viral Diseases: A Meta-Analysis of Placebo Randomized Controlled Trials

Abstract: Background and Objective:Recently, in the scramble to find drugs to treat COVID-19, chloroquine (CQ) and its derivative hydroxychloroquine (HCQ) have rapidly gained the public's attention. In this study, we conducted a meta-analysis of randomized clinical trials (RCTs) to evaluate the efficacy and safety of CQ and HCQ in the treatment of viral diseases. Methods:We searched PubMed, EMBASE, Cochrane Central, Web of Science, Clinical Trials Registries, CNKI, Wanfang Data, CQVIP, and Preprint Servers through April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Yet, HCQ, CQ, AZI and LOPI are frequently used in COVID-19 with its array of inner risk factors. They bear a significant risk of cardiac ADRs [46]. Notwithstanding the need to foster investigation on putative treatments, the safety profile of drugs should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, HCQ, CQ, AZI and LOPI are frequently used in COVID-19 with its array of inner risk factors. They bear a significant risk of cardiac ADRs [46]. Notwithstanding the need to foster investigation on putative treatments, the safety profile of drugs should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine compared to control group was found to be associated with a longer time to clinical recovery in both non‐RCTs/cohort study subgroup as well as in the RCT subgroup (Figure S2 in Appendix ). Two recent meta‐analyses conducted by Ren et al and Wang et al found that patients taking chloroquine or hydroxychloroquine had more adverse events compared to patients assigned to placebo group 64,65 . Another meta‐analysis published a couple of months ago by Sarma et al 66 found no association of hydroxychloroquine with virological cure, death or clinical worsening and safety in nCOV‐2019 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analyses conducted by Ren et al and Wang et al found that patients taking chloroquine or hydroxychloroquine had more adverse events compared to patients assigned to placebo group. 64,65 Another meta-analysis published a couple of months ago by Sarma et al 66 found no association of hydroxychloroquine with virological cure, death or clinical worsening and safety in nCOV-2019 patients. Similar findings on hydroxychloroquine with or without azithromycin were observed from another meta-analysis of five trials which although did observe a trend but the results were not found to be statistically significant in terms of negative conversion of nCOV-2019 (odds ratio [OR] 1.95; 95%CI 0.19 to 19.73) and reduction in progression rate (OR 0.89 95%CI 0.58 to 1.37).…”
Section: F I G U R Ementioning
confidence: 99%
“…A recently published multinational registry analysis on 96,032 nCOV-2019 patients observed that Hydroxychloroquine and Chloroquine were associated with an increased risk of in-hospital mortality (96). Two recent meta-analyses conducted by Ren L et al 2020 and Wang J et al 2020 found that patients taking Chloroquine or Hydroxychloroquine had more adverse events compared to patients assigned to placebo group (97,98). Another meta-analysis published last month by Sarma et al 2020 found no association of Hydroxychloroquine with virological cure, death or clinical worsening and safety in nCOV-2019 patients (99).…”
Section: Discussionmentioning
confidence: 99%